PENGARUH DESAIN KEMASAN, VARIASI PRODUK, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN - Allya Ramadhina; Mugiono, Mugiono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Business competition in the food and beverage industry is not easy and is getting tougher. Competition makes consumers have a variety of choices and are more selective in choosing the products to buy. The purpose of this study is to identify the effects of packaging design, product variation, and product quality on the intention of consumers to purchase Bluder Cokro products. This research is categorized as explanatory study since it explains the causal relationship between variables through hypothesis testing. The sample of this research was selected using purposive sampling method and non-probability sampling technique. With the criteria of people with the minimum age of eighteen years who live in East Java and are interested in the products of Bluder Cokro, 120 respondents were acquired. The data was harvested through Likert-scaled questionnaires and tested using validity and reliability tests. The hypotheses were tested using t test, and the data analysis was performed in SPSS 21. This study finds that packaging design, product variation, and product quality significantly influence purchase intention both partially and simultaneously. Furthermore, product variation is the most dominant factor as it has the highest beta coefficient and t statistics values. Bluder Cokro has been successful in making prospective customers buy their products over the products of other brands.